Aktivitas dan Karakter Kitinase Isolat Trichoderma sp. W34 A4 Asal Kepulauan Raja Ampat Papua Barat - Nunuk Widhyastuti; Muhammad Ilyas (Fakultas Biologi | Universitas Jenderal Soedirman, 2012)
The study of chitinase activity was conducted on 13 selected fungal isolates Trichoderma sp. from Raja Ampat, West Papua and Mount Bromo, East Java. The result showed that fungal isolate Trichoderma sp. W34 A4 isolated from Raja Ampat has the highest chitinase activity (14.3 x10-3 U/ml). The highest chitinase was produced by Trichoderma sp. W34 A4 grown on the media containing colloidal chitin (1%), polypepton (0.1%), KH2PO4 (0.1%) and MgSO4.7H2O (0.05%) for 2 days of incubation. Those isolates produced high chitinase with initial pH range 3.0-8.0 and levels of colloidal chitin between 0.2% -2.0%. Chitinase of Trichoderma sp. W34 A4 has optimal activity at pH 5.0 and in temperature 45 °C. Chitinase from those isolate stable at a wide pH range but it is not stable to the high temperatures.